More than friends - Singleton, Kat (Amara, an imprint of Entangled Publishing, 2026)
"Jude Kensington is the playboy of Pembroke Hills Country Club and the last person I expected to be living with this summer. Charming flirt. Billionaire bachelor. And my friend who once kissed me during a night neither of us can remember-or forget. But before things could get complicated, a surprise showed up on his doorstep. A baby. His baby. With no clue how to care for an infant and me in search of a place to live, we strike a deal: I'll help him survive fatherhood, and he'll give me a place to stay. Temporary. Convenient. Totally platonic. Except nothing about this arrangement feels simple. Not when I'm rocking his daughter to sleep. Not when I catch him watching me like I'm something he can't have. And definitely not when I remember exactly how it felt to kiss him. Falling for Jude was never part of the deal. But the longer we play house, the harder it is to pretend I don't want to be more than friends..."